Exploring the Mind-Body Connection: Yoga, Mindfulness, and Mental Well-Being in Adolescent Physical Education - Alicia Cerdá; Salvador Boned-Gómez; Salvador Baena-Morales (MDPI AG, 2023)
In light of the escalating mental health problems witnessed in recent years, the World Health Organization (WHO) is actively seeking ways to enhance mental health, with an overarching goal to promote mental well-being. Central to this objective is the significant role played by education. As stated by the UNESCO, educational institutions can play a pivotal part in fostering aspects like psychological well-being. Particularly, Physical Education stands out as it addresses specific content related to mental health. Therefore, this study aimed to evaluate the construct of emotional awareness in adolescents and determine whether it is affected by an intervention based on yoga and mindfulness. The study was conducted with a sample of 149 participants, with an average age of 14.6 ± 0.5 years. A quasi-experimental study design was employed, where measurements were taken before (pre) and after (post) the implementation of an intervention with two groups, a control group and an experimental group. The control group underwent a six-session body expression teaching unit, while the experimental group followed the same unit but began with a warm-up based on yoga and mindfulness. The assessment instrument used was the revised Emotional Awareness Questionnaire (EAQ30). To assess the normality of the dataset, the Kolmogorov-Smirnov test was carried out, which indicated a non-parametric sample. Subsequently, the Mann-Whitney U test was executed, revealing no significant differences in any dimension. The Wilcoxon signed-rank test was also conducted, which showed significant differences in two dimensions. The lack of significant results could potentially be attributed to the short duration of the study. Nevertheless, these findings could contribute valuable insights towards understanding the integration of yoga or mindfulness-based programs in Physical Education. These programs have the potential to significantly impact adolescent emotional awareness and mental health, which is particularly crucial given the increasing prevalence of mental health issues in this age group. Therefore, despite the absence of robust findings in this study, it illuminates the necessity and value for further research into the utilization of yoga and mindfulness in the educational context.